Liquid Gold - Katrice Bridges Copeland (Washington University Law Review, 2020)
This Article deals with fraudulent practices in the residential drug treatment industry. It will principally focus on the two related issues of quality of care and patient brokering. The lack of regulation in the residential drug treatment industry is practically an invitation for deceptive business practices such as patient brokering, insurance fraud, and substandard care. While many scholars have written articles addressing the opioid crisis and the best way to address it, this is the first article to address the corruption in the residential drug rehabilitation market. This Article argues that the government must address the crisis in the residential drug treatment industry with national legislation.
Keywords: Liquid gold; Residential drug treatment; Drug treatment; Patient brokering; Opioid crisis; Drug rehabilitation; Insurance fraud